Altered levels of complement components associated with non-immediate drug hypersensitivity reactions - Feng Wang; Liping Huang; Junfeng Yu; Dandan Zang; Liangping Ye; Qixing Zhu (Journal of Immunotoxicology, 2020)
Nonimmediate drug hypersensitivity reactions (niDHRs) range from mild-type maculopapular exanthema (MPE) to severe type Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) with unentirely clarified pathogenesis. This study sought to explore whether complement components participated in niDHRs. The participants comprised of three groups as follows: MPE (n = 65), SJS/TEN (n = 13, contains 7 SJS, 2 SJS-TEN overlap and 4 TEN), and equal healthy controls (n = 78). Skin pathological changes were confirmed by hematoxylin and eosin staining. The mRNA and protein levels of complement components were assessed. In the MPE group, there were no alterations in complement components at the protein and mRNA levels found except for a decrease in factor H mRNA. In the SJS/TEN group, up-regulated levels of C3aR and C5aR mRNA and down-regulated factor H mRNA levels in blood were noted. A lower plasma protein level of C3, Factor H and a higher level of C3a, C5, C5a, C5b-9, Factor B (p < 0.05) were found in the SJS/TEN group compared with in the control (p < 0.05). In SJS/TEN skin lesions, indirect immunofluorescence assays showed positive specific staining for C5b-9, but not C3. Both C3aR and C5aR were positive staining in the SJS/TEN samples, while staining for C1q, mannose-binding lectin (MBL), Factor B, and Factor H were only weak or negative. The findings reported here are the first to define the expression profiles/extent of the presence of various complement components at the mRNA and protein levels in niDHRs, especially in SJS/TEN. These altered complement components might, at least in part, be integral to the mechanisms underlying the pathogeneses of SJS and TEN.